Economics, governance and law : essays on theory and policy - Samuels, Warren J. (Cheltenham: Edward Elgar Pub, 2002)
The book examines some of the fundamental issues in political economy in a non-judgmental and non-ideological way. The political economy is a process of decision making and these papers attempt to identify the deepest levels of conduct of collective choice. These include official and private government, the 'rule of law', the nature of property, rule and markets, deliberative and non-deliberative choice, and the operation of selective perception and of intellectual fraud in politics.
Includes bibliographical references and index.
rpm 03/02/14
Loans
Keywords: Economics; Political science; Law -- Philosophy